2017
DOI: 10.1121/1.4980138
|View full text |Cite
|
Sign up to set email alerts
|

Speech production and sensory impairment in mild Parkinson's disease

Abstract: Little is known about speech-related sensory systems and the link to speech in Parkinson's disease (PD). This study investigates auditory and somatosensory acuity and their association to speech in PD, using /s/ and /ʃ/ as speech targets. Ten adults with mild PD and ten age- and gender-matched healthy participants performed three tasks. In the auditory task, participants discriminated three aperiodic sounds acoustically modified from /s/ and /ʃ/ and differing in spectral shapes. In the tactile task, they judge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Parkinson's disease (PD) is the second most common neurodegenerative disease, and approximately 60,000 people are diagnosed every year in the USA alone; similar incidence rates are reported in Europe (Tanner and Goldman, 1996). Typical characteristic PD symptoms include tremor, rigidity, bradykinesia, and postural instability; critically for this project, voice and speech quality degradation has also been well documented in the PD research literature (Logemann et al, 1978;Harel et al, 2004;Ho et al, 1998;Skodda et al, 2009;Tsanas, 2012;Tsanas et al, 2012;Chen and Watson, 2017). Existing tests for PD assessment and monitoring require the physical presence of the person in the clinic and rely on expensive human expertise.…”
Section: Introductionmentioning
confidence: 90%
“…Parkinson's disease (PD) is the second most common neurodegenerative disease, and approximately 60,000 people are diagnosed every year in the USA alone; similar incidence rates are reported in Europe (Tanner and Goldman, 1996). Typical characteristic PD symptoms include tremor, rigidity, bradykinesia, and postural instability; critically for this project, voice and speech quality degradation has also been well documented in the PD research literature (Logemann et al, 1978;Harel et al, 2004;Ho et al, 1998;Skodda et al, 2009;Tsanas, 2012;Tsanas et al, 2012;Chen and Watson, 2017). Existing tests for PD assessment and monitoring require the physical presence of the person in the clinic and rely on expensive human expertise.…”
Section: Introductionmentioning
confidence: 90%
“…Cognitive changes and self-regulatory deficits often increase as the disease progresses resulting in individuals with PD not always being aware of their voice sound level which contributes to difficulties with long-term transfer of voice intervention effects. 13,14 Changes in auditory perception of one's own voice sound level and in somatosensory processing, with a reduced ability to use auditive feedback to update feedforward mechanisms, result in an underestimation of the required effort needed to produce a sufficient voice sound level as well as decreased regulation of the vocal motor system during ongoing speech. [15][16][17] In 2017, HiCommunication, a new intervention program in a group format for people with PD targeting speech and communication was developed.…”
Section: Introductionmentioning
confidence: 99%
“…The electromyographic evidence confirms the hypertonicity of laryngeal muscles at rest in PD and the evidence for improved respiratory function, prosodic pitch, loudness variation, and speech intelligibility with levodopa treatment [2][3][4][5]; however, other studies have been unsuccessful to draw a causal relationship between dopamine and speech disorders in PD. It has been suggested that, in contrast to the classical motor features of PD, speech disturbances may be due to altered nondopaminergic or special dopaminergic mechanisms, which impair internal cueing, sensorimotor gating, scaling of movement parameters, and attention to action, causing poor regulation of speech initiation, amplitude, and timing [5][6][7]. Speech impairment in PD originates from a blend of motor and non-motor deficiencies because speech is a difficult task coordinated by complex motor and sensory neural networks [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that, in contrast to the classical motor features of PD, speech disturbances may be due to altered nondopaminergic or special dopaminergic mechanisms, which impair internal cueing, sensorimotor gating, scaling of movement parameters, and attention to action, causing poor regulation of speech initiation, amplitude, and timing [5][6][7]. Speech impairment in PD originates from a blend of motor and non-motor deficiencies because speech is a difficult task coordinated by complex motor and sensory neural networks [6][7][8][9]. Speech Disorders affect 75% to 95% of PD patients [10].…”
Section: Introductionmentioning
confidence: 99%